PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alvino, Rahmat; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The purpose of this study was to determine the effect of capital structure on profitability in automotive and component sub-sector companies listed on the Indonesia Stock Exchange. Capital structure as an independent variable was measured using the ratio of Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Longterm Debt to Assets Ratio (LDAR), and Longterm Debt to Equity Ratio (LDER). While profitability as the dependent variable is measured by the ratio of Return on Equity (ROE) and Return on Investment (ROI).In this study, data on the place of financial statements and annual reports. Sampling was carried out by purposive sampling, the samples were 8 of 13 automotive and component companies listed on the Indonesia Stock Exchange. The analysis technique in this study is simple linear, coefficient of determination, t test. Data analysis used linear regression analysis with the help of SPSS 21 software. The results of this study indicate that the test of simple regression analysis of capital structure variables consisting of DAR, DER, LDAR, LDER, the occurrence of a negative relationship to the ROE and ROI profitability variables. This means that the capital structure partially has no effect on profitability in the automotive and component sub-sector companies.Keywords: Capital Structure, Profitability